Розвиток страхового ринку України в умовах воєнного стану - Качула, Світлана Валентинівна; Kachula, Svitlana; Бєлякова, Каріна Олександрівна; Bieliakova, Karina (Чорноморський національний університет імені Петра Могили, ТОВ `"ДКС Центр`", 2024)
У статті розглянуто страхування, як фінансовий механізм захисту від ризиків, який передбачає матеріальну компенсацію в разі настання непередбачуваних подій. Наголошено на важливості страхування для забезпечення фінансової стабільності громадян і бізнесу. Визначено страховий ринок, як систему економічних відносин між учасниками страхових угод, основним об'єктом яких є страховий захист та який є частиною фінансового ринку, де відбувається купівля-продаж страхових продуктів. Розглянуто чинники на мікро- та макрорівневих під впливом яких формується ринок страхових послуг та які визначають розвиток ринку і вимагають комплексного підходу до його аналізу. Розглянуто проблеми, з якими стикаються страхові компанії під час військового стану та проаналізовано основні показники діяльності страхового ринку в 2020-2023 роках, які показали несприятливі зміни, особливо у порівнянні з довоєнними показниками. Встановлено, що з метою підтримки фінансової стійкості страхових компаній на страховому ринку важливо зберігати резерви та забезпечувати ліквідність, а інвестиційна політика повинна бути орієнтована на низькоризикові активи The article deals with insurance as a financial mechanism of risk protection, which provides material compensation in case of unforeseen events. The main areas of insurance are defined, in particular, property, personal, liability, and medical insurance. The importance of insurance to ensure the financial stability of citizens and businesses is emphasized. It was noted that changes in society and Ukraine's course towards European integration affect the development of the country's insurance market. The insurance market is defined as a system of economic relations between the participants of insurance agreements, the main object of which is insurance protection and which is part of the financial market where the purchase and sale of insurance products takes place. The level of development of the insurance market is assessed by absolute and relative indicators that help analyze the efficiency and financial condition of insurance companies. Factors at the micro and macro levels that influence the formation of the insurance services market are examined. At the micro level, competition between insurance companies, changes in customer needs, marketing strategies, and technological innovations are important. At the macro level, the key factors are economic conditions, socio-cultural changes, globalization, natural disasters, and the geopolitical situation. These factors determine market development and require a comprehensive approach to analysis. The problems faced by insurance companies during martial law were considered, and the main indicators of the insurance market in 2020-2023 were analyzed, which showed unfavorable changes, especially in comparison with pre-war indicators. During martial law (2022-2023), only 5% of companies operated stably and without complications; about 60% continued their activities but faced certain difficulties; almost 30% had to stop work and only partially resumed it, while another 10% were unable to resume operations. It was established that in order to maintain the financial stability of insurance companies in the insurance market, it is important to maintain reserves and ensure liquidity, and the investment policy should be focused on low-risk assets.
Development of Ukraine's insurance market under martial law
Keywords: страхування; Insurance; страховий ринок; insurance market; абсолютні і відносні показники страхового ринку; absolute and relative indicators of the insurance market; чинники розвитку страхового ринку; factors of insurance market development; страхові ризики; insurance risks; воєнний стан; state of war